Return of the Solow Paradox? IT, Productivity, and Employment in U.S. Manufacturing - Daron Acemoglu; David Autor; David Dorn; Gordon H. Hanson; Brendan Price (Institute for the Study of Labor (IZA), 2014)
An increasingly influential technological-discontinuity paradigm suggests that IT-induced technological changes are rapidly raising productivity while making workers redundant. This paper explores the evidence for this view among the IT-using U.S. manufacturing industries. There is some limited support for more rapid productivity growth in IT-intensive industries depending on the exact measures, though not since the late 1990s. Most challenging to this paradigm, and our expectations, is that output contracts in IT-intensive industries relative to the rest of manufacturing. Productivity increases, when detectable, result from the even faster declines in employment.
Keywords: O3; J2; L6; 330; productivity; IT capital; employment; Solow paradox; Industrie; Computerunterstützung; Produktivität; Informationstechnik; Technischer Fortschritt; Fertigungsberufe; Beschäftigungseffekt; USA